EVALUASI KAPASITAS SISI UDARA BERBASIS RUNWAY OCCUPANCY TIME PADA BANDAR UDARA SULTAN SYARIF KASIM II PEKANBARU - Michael Exaudi Siregar; Leo Sentosa; Muhamad Yusa; Ari Sandhyavitri; Gunawan Wibisono; Ferry Fatnanta (Racic : Rab Construction Research, 2026)
Sultan Syarif Kasim II Airport serves as the main gateway to Pekanbaru City and is planned as a primary hub airport. This study evaluates the existing airside capacity, runway–taxiway limiting factors, traffic forecast, and capacity improvement alternatives. The analysis used airside geometry data, field operational observations, annual aircraft movements, and socioeconomic data. The results show that traffic is dominated by narrow-body jets; therefore, the capacity limitation is mainly affected by the inefficient runway–taxiway configuration, which increases runway occupancy time. The existing mixed-operation capacity is 15 movements/hour, equivalent to 43,800 regular movements/year. The proposed development alternatives can increase the capacity to 30 movements/hour, equivalent to 125,925 regular movements/year.